PENGARUH KAPASITAS DAN ETOS KERJA PENYULUH PERTANIAN TERHADAP KINERJA PENYULUHAN PERTANIAN DI KOTA KENDARI - Syahrul Alhadi; Weka Widayati; Hartina Batoa (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Agricultural extension workers play a crucial role in facilitating technology transfer, strengthening farmer capacity, and supporting agricultural development. The effectiveness of extension services is significantly influenced by the capacity and work ethic of extension workers. This study aims to assess the level of extension capacity, work ethic, and performance of agricultural extension workers and to examine the influence of capacity and work ethic on their performance in Kendari City, Indonesia. A census approach was used involving all 49 agricultural extension workers working at the Agricultural Extension Center and the Department of Agriculture in Kendari City. Data were collected through a structured questionnaire and analyzed using descriptive statistics and Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS software version 4.0. The results showed that extension workers demonstrated high levels of extension capacity (mean score = 3.8), work ethic (mean score = 3.7), and performance (mean score = 3.7). The SEM-PLS analysis revealed that Extension Capacity had a positive and significant effect on improving extension worker performance. This also applies to the work ethic of agricultural extension workers, which has a positive and significant impact on their performance. The stronger an extension worker's capacity, the higher their performance. Similarly, a strong work ethic leads to higher performance. Implementing extension services with extension workers who have a high level of capacity and work ethic can improve their performance, which in turn can impact overall productivity.